Budidaya Maggot Lalat BSF: solusi limbah dan peningkatan pendapatan masyarakat Desa Bakalan - Afandi, Achmad; Susanto, Ratno; Indah, Chindy Hanggara Rosa; Hadiwiyanti, Rizka; Sugiyanto, Hadi; Widayanti, Isro Ani; Fadilah, Muhammad Reza Ishadi (Universitas Hamzanwadi, 2023)
Bakalan Village, experiencing a significant increase in organic waste production, faces challenges in waste management due to the absence of a Temporary Disposal Site (TDS). This study investigates the implementation of Black Soldier Fly (BSF) maggot cultivation in Bakalan Village, Purwosari Subdistrict, Pasuruan District, East Java, as an innovative solution for organic waste management and an alternative income source. This community service program was initiated to provide training and insight to the village residents about the economic potential of BSF maggot cultivation. The activity involved 46 village residents and was conducted on July 5, 2021, introducing maggot cultivation techniques and their use as an alternative feed for livestock. The results indicate a reduction in the volume of organic waste in the village and an increased awareness among the community about the economic value of organic waste. Dried and further processed maggots showed an increase in selling price from IDR 8,000 to IDR 30,000 - IDR 40,000 per kilogram. This study highlights the link between sustainable waste management and local economic development, providing insights into BSF maggot cultivation practices as an effective method to reduce organic waste and increase the income of the residents in Bakalan Village.